Plant based nugget innovation based on oyster mushrooms (Pleurotua ostreatus) and corn flour (Zea mays var amylacea) as high fiber foods: Inovasi Plant Based Nugget berbasis Jamur Tiram (Pleurotua ostreatus) dan Tepung Jagung (Zea mays var amylacea) sebagai Pangan Tinggi Serat - Ramadhani, Aqilah Wulan; Talitha, Zada Agna; Ramanda, Muhammad Rizky (Universitas Slamet Riyadi Surakarta, 2025)
Indonesia has many types of junk food that have a strong taste, but are generally not nutritionally balanced, namely high in fat, salt, or sugar and low in fiber. One of the most popular is nuggets which are generally made from meat. As a healthier alternative, nuggets are made using oyster mushrooms which are low in fat and higher in fiber, and combined with gluten-free and high-fiber corn and tapioca flour to replace wheat flour which contains gluten. This study aims to determine the effect of the combination of corn and tapioca flour on the physicochemical characteristics of oyster mushroom nuggets. This study used a Completely Randomized Design (RAL) with 5 treatments in duplicate. The formulation was used with a combination of corn and tapioca flour, namely 60: 0 (P1), 45: 15 (P2), 30: 30 (P3), 15: 45 (P4), and 0: 60 (P5). The results of the analysis have an effect (P <0.05) on chemical characteristics with a range (db%) of ash content of 3.9% -4.71%; fat content 1.37% - 7.76%; protein content 6.79% - 18.79%; carbohydrate content 71.46% - 77.43%; crude fiber 3.9% - 8.27%, and on physical characteristics with a textured range of 1.1N-2.69 N; color L 50.55- 53.73; color a 2.78- 4.64; color b 10.89-13.71. The implications of this study indicate that online substitution into mushrooms with a combination of corn flour and tapioca can affect the nutritional value and quality of nuggets.